Arkivetnografi eller Reflektioner över en tappad biljett - Lennartsson, Rebecka (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2014)
Ethnologists are schooled in ethnographic thinking and ethnographic methods. Experience has always been an effective guarantee of ethnographic authority. The characteristics of ethnography, however, are no different for an ethnologist working with historical material. In my experience working methods are often similar too, not least because the method, regardless of field, is based from beginning to end on text in its widest sense, which requires writing in all its various forms. In this article, a lost note, used as evidence in a trial, functions as a starting point for discussing the role of the written word when an ethnologist looks at historical material in order to conduct ethnography in the past. The note is a short extract from the court records concerning a trial against the notorious procuress L. von Plat in 18th century Stockholm. The story is part of my research project that looks at the trade in sexual services in 18th-century Stockholm. Trying to become familiar with the cultural pixels of the period has proved challenging. Despite possessing a detailed material that in many ways approaches the individuals themselves, during the course of my work I have sometimes felt the frustration of never really managing to rise above street level. I continually risk losing myself in the material, going astray in the lanes. The ability of the small-scale perspective to identify flaws, contradictions and cultural diversities is, in my opinion, one of the main advantages of the ethnographic method of attack. Yet to find explanations to questions that arise, a wider context is needed. The aim of the project stretches beyond narrating a number of events and fates from a lost reality. It extends to trying to formulate theories to explain how marginalization processes act and endure over time.